Self-perceived health status in older adults: regional and sociodemographic inequalities in Spain - Beatriz Fernandez-Martinez; Maria-Eugenia; Maria João Forjaz; Gloria Fernández-Mayoralas; Fermina Rojo-Pérez; Pablo Martínez-Martín (Universidade de São Paulo, 2012)
OBJECTIVE: To assess regional and sociodemographic differences in self-perceived health status among older adults. METHODS: A face-to-face quality of life survey was conducted in a representative sample of the Spanish population comprising 1,106 non-institutionalized elderly aged 60 or more in 2008. Logistic regression models were used to explain self-perceived health status according to the EuroQol Group Visual Analogue Scale (EQ-VAS). Independent variables included sociodemographic and health characteristics as well as the nomenclature of territorial units for statistics level 1 (NUTS1: group of autonomous regions) and level 2 (NUTS 2: autonomous regions). RESULTS: Younger and better off respondents were more likely to have a positive self-perceived health status. Having no chronic conditions, independence in performing daily living activities and lower level of depression were also associated with positive self-perceived health status. People living in the south of Spain showed a more negative self-perceived health status than those living in other regions. CONCLUSION: The study results point to health inequality among Spanish older adults of lower socioeconomic condition and living in the south of Spain. The analysis by geographic units allows for international cross-regional comparisons.